Effectiveness study of a new type of control chart for process quality control : the synthetic control chart - Phua, Hong Yee. (2008)
This project aims at developing and testing the effectiveness of the Synthetic Control Chart, which inherits characteristics of both the Shewhart X Chart and the Conforming Run Length (CRL) chart.